ISOLATION AND CHARACTERIZATION OF MDR BACTERIA FROM IN VITRO CULTURE OF BACOPA MONNIERA AND SUPPLEMENTATION OF NATURAL EXTRACTS TO CONTROL BACTERIAL CONTAMINATION - Sharma, Yash; Bhardwaj, Manish; Nagar, Anshita; Bhagat, Neeta (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The purpose of the present study was to isolate and characterize bacterial contamination from in vitro culture of Bacopa monniera callus culture. Methods: The two selected isolates (1 and 2) were identified by morphological, biochemical and molecular (16S rRNA gene sequencing) methods. Beside this antibiotic resistance was also determined. Results: The isolates were identified as closely related to Enterobacter cloacae (KU350623) (Isolate 1) and Myroides odoratimimusÂ (KU382740) (Isolate 2). The isolate 1 and 2 were found to be resistant to streptomycin (25 mcg), dapsone (10 mcg), erythromycin (15 mcg), chloroamphenicol (25 mcg) and ampicillin (10 mcg). Supplementation of the natural extract was tested to control the contamination due to these multi drug resistant bacteria. Aqueous and alcoholic leaf extracts of Azadirachta indica was added to plant tissue culture media i.e. MS media in order to control contamination. Conclusion: The present studies suggest using natural extracts supplementation as a promising strategy to control the in vitro bacterial contamination in plant tissue culture.